Discrepancy of Real Tariffs with INA-CBG’S for Dengue Haemorrhagic Fever Patients in a Hospital in Sidoarjo 2019 - Marthy Meliana Ariyanti Jalmav; Amelia Lorensia; Suyanto Suyanto; Achmad Syahrani (Budapest International Research in Exact Sciences (BirEx) Journal, 2021)
Dengue Hemorrhagic Fever (DHF) patients in Indonesia reached 129,650 cases with a death toll of 1,071 people in 2015. DHF puts an economic burden on the community and government. This study aims to determine the difference in real cost tariffs and INA CBG's for DHF in a hospital in Sidoarjo, East Java. This cross-sectional study applied a descriptive design, conducted from January to December 2019. The data in this study consisted of characteristic data and differences in real hospital tariffs and INA CBG tariffs for DHF in the hospital treatment room. 625 hospitalized cases were included in this study. This hospital underwent a deficit (loss) of 30% from the difference between the total INA CBG's package tariffs and the total real hospital tariffs in 2019. There is a negative difference between the real hospital tariffs and the tariffs according to INA CBG's in the treatment of dengue fever in a hospital in Sidoarjo which produces losses for the hospital.